1998
DOI: 10.1088/0967-3334/19/4/002
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the spatial relationship between complexity and motility within the oesophagus

Abstract: Nonlinear analysis techniques have recently been used in the characterization of complex physiological signals seen in pathological disorders such as epilepsy and cardiac fibrillation. In this study a series of controlled swallows from an asymptomatic demonstration group was investigated using oesophageal manometry. The nonlinear measure of complexity, largest Lyapunov exponents and phase portraits were then used to explore the complexity of motility patterns at different points within the oesophagus. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In further studies more advanced approaches to signal processing and computer programming could be applied; for example automated pre-processing packages [26,27], cubic B-splines [28] or largest Lyapunov exponents [10]. In addition, ''unsupervised'' ANNs, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In further studies more advanced approaches to signal processing and computer programming could be applied; for example automated pre-processing packages [26,27], cubic B-splines [28] or largest Lyapunov exponents [10]. In addition, ''unsupervised'' ANNs, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Haylett et al [10] used non-linear chaos theory to assess and quantify oesophageal motor dysfunction; it was concluded that for the classification of oesophageal motor disorders, especially DOS and non-specific oesophageal motility disorders, such non-linear techniques may be superior to conventional techniques. Artificial neural networks (ANNs) are mathematical models that use non-linear statistical analysis to elucidate previously unrecognized relationships between given input variables and an output variable [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, our previous work examining the nonlinear nature of oesophageal peristalsis has highlighted that the complexity of oesophageal peristalsis varies widely between asymptomatic subjects (Haylett et al 1998). The analyses of these multidimensional data represent a major challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The events were analysed for the pressures recorded at the 2 nd transducer, midway in the smooth muscle of the oesophagus. Measurements of pressure above this point may be more complex as a result of the initialisation of the swallow and impact of striated muscle [5]. Measurements below this point towards the distal oesophagus may have additional complexity as a result of the sphincter between the oesophagus and stomach.…”
Section: Analysis Using the Kohonen Sofmmentioning
confidence: 99%